Analisis Kemunculan Indikator Literasi Membaca pada Lembar Kerja Peserta Didik (LKPD) Berbasis Model RADEC di SD Laboratorium Percontohan UPI Kampus Purwakarta - Indra Suhendra; Wahyu Sopandi; Udin Syaefudin Sa'ud; Hany Handayani; Nanda Willian; Yusup Maulana; Indra Gunawan (Jurnal Elementaria Edukasia, 2023)
This study aims to analyze the occurrence of reading literacy indicators in a set of Student Worksheets (LKPD) for elementary school students (grades 2, 3, 4, and 5) based on the Read, Answer, Discuss, Explain, Create (RADEC) model at UPI Campus Purwakarta Laboratory Elementary School. A case study methodology was employed in this research. The analysis results demonstrate the dominance of Informational Texts in almost all cases, emphasizing the importance of mastering factual information in reading literacy. Personal and cultural contextual texts also play a central role in developing reading skills. On the other hand, in the cognitive process, the elements of evaluating and reflecting on information play a key role in advancing reading literacy. The research findings provide in-depth insights into the dynamics of learning in various classes and subjects. The implications of this analysis indicate the need to develop more focused and effective learning strategies, taking into account the unique characteristics of each class and subject. By expanding the scope of reading literacy understanding through diverse texts, including fiction, and integrating personal, social, and scientific dimensions, reading education at the elementary level can continue to evolve. This research serves as a starting point in the journey towards more empowered and integrated reading literacy education at UPI Campus Purwakarta Laboratory Elementary School.